Investigation on the stability, microstructure, and rheology of E2 protein-stabilised pickering emulsion gel - Ariyani, Novenia Oerip (2018)
Rheology properties of structured fluids, such as emulsion, are closely associated with their microstructure arrangements. Investigation of the rheology behaviour and microstructure of emulsion system provides a more profound understanding of its physical characteristics and potential application. Self-assembled E2-protein nanocage has been successfully employed as a Pickering emulsifier in an oil-in-water emulsion system. A specific oil/water ratio composition of the Pickering emulsion produced an emulsion gel with viscoelastic behaviour that is desirable in cosmetic formulation. However, there has been no further characterisation of the Pickering emulsion gel dynamic physical properties and microstructure. In this project, we performed a deeper investigation of the emulsion gel rheological properties using dynamic mechanical analysis and microstructure formation through electron microscopy observation. Experiments were conducted on the Pickering emulsion gel with different oil/water ratio compositions or various storage gelation temperatures. All formulated E2-stabilised Pickering emulsion gels demonstrated shear thinning and solid-like behaviour that is similar to the viscoelastic characteristic of commercialised creams and lotions. Network connection among the dispersed droplets of the emulsion gel system was also observed in the electron microgram obtained using Transmission Electron Microscopy (TEM) and Field Emission Scanning Electron Microscopy (FESEM) to confirm the solid-like structure of the system. These characteristics of the Pickering emulsion gel are of potential benefits in cosmetic products. Our study provides as a foundation for optimisation of E2-stabilised Pickering emulsion gel application in cosmetic formulation.